Rendimiento académico y estado emocional en un niño con discapacidad intelectual. - Cocheres Paladines, Dayana Mishel; Cuenca Cely, Angie Dayana (Machala, Utmachala, 2023)
The present research work had as object of study a child with intellectual disability, making reference to the significant limitations in cognitive functioning as well as in the development of adaptive skills, from the analysis of academic performance and emotional states. Therefore, the general objective is to determine the relationship between academic performance and emotional state in a child with intellectual disability. This research is descriptive, since it is focused on the characteristics and qualities of the case study, from Piaget's cognitive approach. For the foundation and collection of information, the instruments used were the structured interview, the neuropsychological maturity questionnaire CUMANES, the CAT-A child apperception test and the Florence Goodenough test, which resulted in the student's academic performance due to neurocognitive difficulties and in terms of emotional state, he shows impulsivity, extreme insecurity, tendency to depression, emotional withdrawal, lack of social interest and shyness; therefore, he tends to withdraw into himself and present impulse inhibition. Thus allowing us to conclude by mentioning that academic performance is related to the emotional state, given that, when he presents high levels of happiness, his educational performance improves due to the positive attitude when performing intra and extracurricular activities, as opposed to when he has negative emotional states, in addition, the intellectual disability of the child is not a limiting factor for the development of educational activities, but rather the overprotection of the legal representative.
El presente trabajo de investigación, tuvo como objeto de estudio un niño con discapacidad intelectual, haciendo referencia a las limitaciones significativas en el funcionamiento cognitivo como también en el desarrollo de las habilidades adaptativas, desde el análisis del rendimiento académico y estados emocionales. Por ello como objetivo general planteado está determinar la relación existente entre el rendimiento académico y el estado emocional en un niño con discapacidad intelectual. Esta investigación es de tipo descriptivo, puesto que, se puntualiza en las características y cualidades del estudio de caso, desde el enfoque cognitivo de Piaget. Para la fundamentación y recopilación de información los instrumentos utilizados fueron la entrevista estructurada, el cuestionario de madurez neuropsicológica CUMANES, el test de apercepción infantil CAT-A y el test de Florence Goodenough; mismos que dieron como resultado que el rendimiento académico del estudiante se da a causa de las dificultades neurocognitivas y en cuanto al estado emocional muestra impulsividad, inseguridad extrema, tendencia a la depresión, retraimiento afectivo, falta de interés social y timidez; por ende, tiende a encerrarse dentro de si mismo y presentar inhibicion de impulsos. Permitiendo así concluir mencionando que el rendimiento académico si tiene relación con el estado emocional, dado que, cuando presenta niveles altos de felicidad su desempeño educativo mejora por la actitud positiva al realizar las actividades intra y extracurriculares a diferencia de cuando tiene estados emocionales negativos, además, la discapacidad intelectual del menor no es limitante para el desarrollo de las actividades educativas sino la sobreprotección del representante legal.
Keywords: RENDIMIENTO ACADEMICO; ESTADO EMOCIONAL; DISCAPACIDAD INTELECTUAL; COGNICION; ADAPTABILIDAD